Effect of a Small Amount of Synthetic Fiber on Performance of Biocarbon‐Filled Nylon‐Based Hybrid Biocomposites. Issue 5 (1st April 2021) - Chang, Boon Peng; Abdelwahab, Mohamed A.; Kiziltas, Alper; Mielewski, Deborah F.; Mohanty, Amar K.; Misra, Manjusri
Abstract: Advanced hybrid biocomposites are engineered from nylon 6, waste wood biosourced carbon (biocarbon) with a low content of synthetic fiber for lightweight auto‐parts uses. The novel engineering process through direct injection molding of only 2 wt% synthetic fibers in the form of masterbatch with 20 wt% biocarbon, results outstanding performance of the resulting nylon biocomposites. Such uniquely developed biocomposites show tensile strength of 105 MPa and tensile modulus of 5.14 GPa with a remarkable heat deflection temperature (HDT) of 206 °C. The direct injection molding of synthetic fiber retains the length ≈3 times higher as compared to traditional extrusion and injection molding; resulting greater degree of entanglement and composite reinforcement effectiveness in the hybrid biocomposites. Highly dimensionally stable nylon 6 biocomposites with a very low coefficient of linear thermal expansion results through reinforcing ability of the sustainable biocarbon and small amount of synthetic fiber. Abstract : Enhancement of mechanical properties of the fiber‐reinforced composites are mostly restricted due to the fiber breakage during extrusion and compounding. In this work, a superior mechanical and thermal properties enhancement of polyamide 6/biocarbon composites co‐reinforced with synthetic fiber (glass fiber or carbon fiber) masterbatch through direct injection molding is presented.